2014
DOI: 10.1002/mabi.201400137
|View full text |Cite
|
Sign up to set email alerts
|

Polymersomes from Polypeptide Containing Triblock Co- and Terpolymers for Drug Delivery against Pancreatic Cancer: Asymmetry of the External Hydrophilic Blocks

Abstract: Well-defined amphiphilic polymers of the ABA and ABC type are synthesized, where A is poly(L-lysine hydrochloride) (PLL), B is poly(γ-benzyl-(d7) L-glutamate) (PBLG(-d7)), and C is poly(ethylene oxide) (PEO). The two polymers exhibit similar PBLG(-d7) composition, while in the ABC, the volume fraction of PEO block is higher than that of PLL. Both polymers form polymersomes in water. The polymersomes are loaded with doxorubicin or paclitaxel. It is found that in the ABC, due to asymmetry of the two hydrophilic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
32
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 55 publications
0
32
1
Order By: Relevance
“…The main advantages of polymer‐based drug delivery systems include enhanced drug bioavailability, lower toxicity, reduced frequency of administration and less chance of side effect occurence . In particular, synthetic polypeptides are receiving immense attention because of their wide use as therapeutic and diagnostic agents and their potential biomedical applications in drug/gene delivery and tissue engineering …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The main advantages of polymer‐based drug delivery systems include enhanced drug bioavailability, lower toxicity, reduced frequency of administration and less chance of side effect occurence . In particular, synthetic polypeptides are receiving immense attention because of their wide use as therapeutic and diagnostic agents and their potential biomedical applications in drug/gene delivery and tissue engineering …”
Section: Introductionmentioning
confidence: 99%
“…Reduction‐sensitive nanocarriers containing disulfide bonds in their structure have also received considerable attention for intracellular drug delivery . This feature is of great promise knowing that these linkages markedly improve the extracellular stability of the nanocarriers and also can be rapidly and selectively cleaved by the highly reductive intracellular environment caused by the presence of the tripeptide glutathione ( γ ‐ l ‐glutamyl‐ l ‐cysteinylglycine, GSH). The concentration of GSH in the cellular interior (cytosol) is known to have a value of around 10 mM, while the extracellular microenvironment possesses a significantly lower concentration (1–2 μM) which is unable to disrupt the disulfide bonds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because they do not provide melting points and yields, it is difficult to validate this procedure. Iatrou et al performed the ring closure in the presence of Et 3 N‐yielding lysine(Boc) NCA with a yield of 60%. Dygert et al reported the use of AgCN in combination with the Fuchs–Farthing method, which leads to the NCA with the highest melting point reported in literature (136–137 °C).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, suitable acid‐labile alternatives for the Z group appear preferable, for instance, the tert ‐butyloxycarbonyl (Boc) group. Surprisingly, the synthesis and application of PLys(Boc) has been reported only in a few publications . One reason seems to be that the NCA synthesis is commonly performed after the Fuchs–Farthing method, which utilizes phosgene for ring closure leading to liberation of 2 equiv.…”
Section: Introductionmentioning
confidence: 99%